PENGORGANISASIAN PENDIDIKAN ISLAM DAN MANAJEMEN SDM DI MI SALAFIYAH DALAM PANDANGAN AL-QUR’AN DAN HADIS - maeemunah; moh.ali; dewi cahyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study explores the organization of Islamic education and human resource management (HRM) at MI Salafiyah Cirebon based on the principles of the Qur’an and Hadith. Using a qualitative descriptive method, data were collected through interviews with the principal, vice principal of student affairs, and teachers, as well as documentation and observation. The findings reveal that MI Salafiyah implements educational organization not only as an administrative process but also as a religious obligation grounded in values of discipline, amanah, and moral responsibility. Organizational practices—including planning, structuring duties, managing teachers, curricula, facilities, and student development—are aligned with Qur’anic principles of order and balance (QS. As-Saff: 4; QS. Al-‘Alaq: 1–5) as well as Prophetic guidance on leadership and accountability. Human resource management is strengthened through the application of Islamic moral leadership, continuous supervision, and character-based development. This integration of Islamic values with modern educational management fosters teacher professionalism, enhances students’ intellectual and spiritual growth, and ensures that the institution operates efficiently while upholding its Islamic identity. The study concludes that MI Salafiyah provides a practical model for implementing Islamic education management by harmonizing spiritual, ethical, and organizational dimensions within a contemporary educational framework.